First, we can take the square root of the term in the denominator giving:
(2sqrt(x) * sqrt(x^3))/(3x^5)
Next, we can use this rule of radicals to simplify the numerator:
sqrt(color(red)(a)) * sqrt(color(blue)(b)) = sqrt(color(red)(a) * color(blue)(b))
(2sqrt(color(red)(x)) * sqrt(color(blue)(x^3)))/(3x^5) => (2sqrt(color(red)(x) * color(blue)(x^3)))/(3x^5) => (2sqrt(color(red)(x^1) * color(blue)(x^3)))/(3x^5) => (2sqrt(x^(color(red)(1)+color(blue)(3))))/(3x^5) =>
(2sqrt(x^4))/(3x^5) => (2x^2)/(3x^5)
We can now use this rule for exponents to simplify the x terms:
x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))
(2x^color(red)(2))/(3x^color(blue)(5)) => 2/(3x^(color(blue)(5)-color(red)(2))) => 2/(3x^3)